Pengaruh Fungsi Permintaan dan Penawaran Terhadap Keseimbangan Pasar - Angga Aryanto Prasetyo; Rizky Maulana Putra (RESWARA: Jurnal Riset Ilmu Teknik, 2023)
This study investigates the influence of demand and supply functions on market equilibrium. Market equilibrium is a fundamental concept in economics, reflecting the point at which quantity demanded equals quantity supplied. This research aims to analyze how variations in demand and supply functions affect equilibrium prices and quantities in competitive markets. Using a quantitative approach, mathematical modeling, and simulation methods, the study examines both linear and nonlinear demand-supply dynamics, including saturation and collectability factors. Data were synthesized from secondary sources, including historical market observations and established economic models. The results indicate that shifts in demand or supply functions can significantly alter equilibrium points, sometimes leading to indeterminacy or multiple equilibria, consistent with the findings of Drewello (n.d.) and Caginalp (2005). Moreover, the study highlights the relevance of dynamic and nonlinear models for understanding real-world market behaviors. Implications include better-informed policy decisions, pricing strategies, and market regulation to maintain stability. Future research may extend to stochastic modeling and agent-based simulations to capture market complexity.